Addressing animal methods bias through government-led initiatives - Kopew, Jessica S.; Ritskes-Hoitinga, Merel; Singer, Mikalah; Trunnell, Emily R.; Vidaurre, Gabby; Krebs, Catharine E. (Frontiers in Toxicology, 2026)
Peer review aims to ensure that high-quality research is funded, conducted, and disseminated. However, peer review bias limits this process by violating impartiality, allowing factors other than merit to influence reviewers’ judgment. Animal methods bias is a peer review bias characterized by a preference for animal-based methods or lack of expertise to properly evaluate nonanimal methods, affecting the fair consideration of animal-free biomedical approaches. To date, most investigations into the characteristics of animal methods bias have relied on self-reported survey data and anecdotes from workshops, but available evidence shows it can impact the likelihood of obtaining funding or achieving positive publication outcomes and may also lead to the unjustified use of animals because of undue pressure caused by reviewer expectations or requests. Globally, progress is advancing in the shift away from animal experimentation and towards human-based, nonanimal methods to improve translation and clinical relevance, but barriers like animal methods bias must be understood and addressed to see these efforts through and reach the full potential of new approach methodologies (NAMs). In 2025, two government-led initiatives were announced to this end, in the United States and United Kingdom. In addition to measures like expanded funding, training, and infrastructure for nonanimal methods, these initiatives also included efforts to address animal methods bias. While global recognition of animal methods bias is encouraging, the implementation and success of these measures remains to be seen, and further strategies to understand and address animal methods bias around the world and throughout the research lifecycle are needed.